The influence of heavy metals on morphological and physiological parameters of Salix clones - Urošević, Jelen; Rodzkin, Aleh; Stanković, Dragica; Trivan, Goran; Jovanović, Filip (Journal of the Belarusian State University. Ecology, 2024)
Three clones of Salix alba and one clone of Salix viminalis were used for research purposes. The research aims to study the influence of heavy metals Ni, Cu, Cr Cd, Pb and As, on morphological (primary and secondary growth) and physiological (rate of photosynthesis, transpiration, water use efficiency) processes and determine the most favourable clone that would have its application in phytoremediation of contaminated soil and productivity of different fast-growing clones, with the aim of energy production. Prospective clones of willow were evaluated based on morphological (plant height, stem diameter, biomass, leaf area) and physiological (photosynthesis intensity and transpiration, stomatal conductance, efficient use of water, intercellular concentration of СО2) parameters. Contamination of soil with heavy metals negatively affected the morphological and physiological characteristics of willow clones. Clones with physiological characteristics less dependent on soil contamination with heavy metals were selected on the results of evaluation. Physiological parameters of clones positively correlated with morphological parameters. Heat of willow biomass combustion planted on contaminated and uncontaminated soils didn’t differ significantly. Among the studied genotypes, two Salix alba clones, namely clones 3 and 4, stand out. The contaminated habitat substantially reduces willow biomass and physiological parameters of willow. Nonetheless, the thermal energy derived from biomass showed no significant variance between contaminated and uncontaminated plants.